Program transport sedimen pada saluran aluvial - ACHMAD, Nizar ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Sediment transport has been an interesting phenomena and can’t be predicted accurately, therefore an arrangement of a tool to calculate forecast in acceptable accuracy is still an object of interest. Unfortunately the current calculation involve reading curves that resulting subjective value, in practice and difficult for iteration calculation. USGS developed Seddich, an application to calculate sediment transport which provide many methods and it made prediction equation for these curves. This application is quite old and still using text based interface, hence need a rejuvenation. This research is intended to upgrade Seddisch by rebuild Seddich on Windows based system and utilize Access database format for data management. To get wider user especially in Indonesia, an additional option made to switch unit of calculation between metric and imperial. A calculation method by KalinskeFrijlink added as it is still used widely. An Additional control added to guide inputting data process that ensure filling data needed for each selected method. An improvement of Einstein method in calculating Integral Einstein is provided by option to use analitical prediction by Guo Julien. Evaluation results that the upgraded program shows the same result for all three data set of samples. The use of metric-imperial switch unit data works well. Kalinske-Frijlink method has worked which result close to Kalinske method. Einstein Integral result close to pervious method, and assumed to give better approximation.